Abscheidung von SiOxNy Sperrschichten durch Dual Magnetron Sputtering: Vergleich von Mittelfrequenz‐ und bipolar gepulsten DC‐Verfahren. (December 2015) - Tinkham, Brad P.
Abstract : Silicon Oxynitride Barrier Layers Deposited by Pulsed‐DC Dual Magnetron Sputtering SiOx Ny barrier layers have been deposited using pulsed direct current (DC) and medium frequency (MF) sputtering on large area (GEN 5) glass substrates. Several process parameters, such as discharge voltage, boost voltage, and discharge frequency were varied with the goal of increasing system productivity and reducing the arc rate during SiOx Ny deposition. The arc rate during operation with pulsed DC dual magnetron sputtering was lower than for MF sputtering; however for the same nominal discharge power, the deposition rate using pulsed DC power supplies was slightly lower than for operation with MF. The suitability for use as a barrier layer was deduced by capping the SiOx Ny layers with DC sputtered ZnO:Al coatings and subjecting the sample stacks to anodic and cathodic degradation and subsequent storage in a damp atmosphere.